Exploring the Personal Factors of Homeless Ex-Prisoners Who Migrated Repeatedly to Kuala Lumpur from the Perspective of Migration Theory by Everett S. Lee/ Meneroka Faktor Peribadi Gelandangan Bekas Banduan Berhijrah Secara Berulang Kali ke Kuala Lumpur dari Perspektif Teori Migrasi oleh Everett S. Lee (Sains Humanika, 2021)
The concentration of homeless ex-prisoners in the capital city raises personal choice factors for them to migrate repeatedly. Kuala Lumpur is the chosen destination for migration for ex-prisoners after their release from prison. The lack of  place to go makes Kuala Lumpur a destination of choice despite living as a homeless person. This qualitative study uses a phenomenological approach involving 15 homeless ex-prisoners to explore the personal factors that led them to choose Kuala Lumpur and resigned to living on the streets. The personal factors identified were self-choice, finding job, having friends, easy access to food, migrating, and being familiar with Kuala Lumpur. The study's findings have confirmed the migration factors brought about by the Migration Theory by Everett S. Lee. This study recommends that the social services and welfare agencies involved, such as the Social Welfare Department, Kuala Lumpur City Hall, and the Prisons Department, to implement more comprehensive and consistent interventions towards assisting homeless ex-prisoners via necessary services, welfare, and appropriate social support.
Keywords: homeless ex-prisoners, personal factors, migration, living on the streets, Kuala Lumpur